200k views
2 votes
Which expression is equivalent to (1/4ab)^-2? Assume a is not equal to 0,b is not equal to 0

a. -1/16a^2b^2
b. a^2b^2/4
c. -16a^2b^2
d. 16a^2b^2

2 Answers

0 votes
The answer would be D. 
User Tong Wang
by
6.2k points
6 votes

Answer:

d.
16a^2b^2

Explanation:

Given expression,


((1)/(4ab))^(-2)


=((4ab)^(-1))^(-2)
\because (1)/(a^m)=a^(-m)


=(4ab)^(-1* -2)
\because (a^m)^n=a^(mn)


=(4ab)^2


=(4)^2(a)^2(b)^2
\because (ab)^m=a^mb^m


=16a^2b^2

Hence, option d is correct.

User MyCarta
by
5.7k points